Topological Analysis of Angular Momentum Range Values of the Gyro Moment Clusters Based on Collinear Gyrodines Pairs - Yefymenko, M.V.; Kudermetov, R.K. (Кибернетика и вычислительная техника, 2019)
The purpose of the article is to develop a technique for detecting singular states in GMC based on three collinear pairs. Results. The analysis was carried out and the singular states of the GMC with three collinear pairs were revealed.